Using multiple lines of evidence to assess recovery potential of a warm water fish population in a cold water impacted river - Tonkin, Zeb; Koehn, John; Commens, Sarah; Hackett, Graeme; Harris, Annique; Kitchingman, Adrian; Lyon, Jarod; Moloney, Paul; Todd, Charles; Woodhead, Jon (Frontiers in Conservation Science, 2023)
Humans have substantially altered landscapes across the globe, generating novel ecosystems with varying states of modification. The principles of reconciliation ecology emphasise that such ecosystems must also be considered for conservation outcomes. This requires an understanding of how anthropogenic habitat alterations in a novel ecosystem may disrupt life cycle processes of key biota, thereby enabling the development of management strategies that may bypass or ameliorate potential bottlenecks in life history stages. We explore this by assessing Murray cod (Maccullochella peelii), a native fish species of considerable cultural, recreational and conservation significance in a severely altered river reach in south-eastern Australia. This species was considered to have disappeared in the reach following alterations to the river’s thermal profile (cold water pollution - CWP), but instead has persisted. We examined the life cycle of Murray cod and use multiple lines of evidence to assess the impacts of CWP pollution on key processes such as adult migration, recruitment and juvenile survival. We also evaluated the potential for recovery and persistence of the species in this novel system using mitigation measures such as flow management and stocking and opportunistically tested their effectiveness. We found the key impact pathway of CWP on the Murray cod population is via its effects on the key processes influencing natural recruitment. Conversely, the effects of CWP on emigration and survival of larger juveniles and adults did not appear to be a major bottleneck for the population. Using a stochastic population model, we showed that the population could be sustained by stocking and opportunistic water management while still meeting irrigation demands. Monitoring to test our recommendations showed natural recruitment and improved survival of stocked fish during years with limited CWP, thereby corroborating our predictions. Our use of multiple lines of evidence to assess a species’ responses to impacts of habitat alteration enabled the formulation of recommendations for management that could then be tested. The success of such actions add to the growing body of literature that shows species of conservation significance can be maintained in novel ecosystems which should be considered within the context of conservation planning across the landscape.